Pengaruh Etika Sosial Terhadap Antisipasi Fintech Lending Ilegal - Khofsoh, Faza Zanuba; Setyaningrum, Latifa Ismi; Saphira, Alicia; Grace, Putri Azarya; Parasetya, Mutiara Tresna (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The rapid development of fintech can lead to illegal fintech, which is caused by fintech lending providers operating in Indonesia with no legal permission from OJK. This study aims to make society literate in public finances, provide broad insight into the role and social ethics of the importance of knowledge in responding to rapid changes in digital technology, especially in thecase of illegal fintech lending, which is currently a public concern. The method in this study used a quantitative method based on the problems that occur in the community by collecting data using an online questionnaire in the form of a likert scale. This study indicated that social ethics has a positive effect on anticipating illegal fintech lending, but financial literacy is not significant for anticipating illegal fintech lending. A person's social ethics can help in determining attitudes and behaviour in management, budgeting, and decisions regarding the form of fintech lending that will later be taken. A person's financial attitude towards intentions can change behaviour in managing finances.